Rol del virus ebstein barr y el carcinoma gástrico: Role of epstein barr virus and gastric carcinoma - Beltrán-Gárate, Brady (2022)
Abstract Gastric cancer (CG) is one of the most common neoplasms in Peru. Recently the molecular subtypes have been typified in CG. A molecular subtype is associated with the Epstein Barr virus. This entity presents with a frequency of 10%, in a non-cardiac region, in male patients and with the diffuse histological subtype. The prognosis is better compared to the other types of CG. It presents its own molecular alterations that in the future could be susceptible to target therapies or immunotherapy. DOI: https://doi.org/10.25176/RFMH.v18.n1.1269